Removal of Interferences from Partial Discharge Pulses using Wavelet Transform - Vidya H.A Vidya H.A; Bindia Tyagi; V Krishnan V Krishnan; K. Mallikarjunappa K. Mallikarjunappa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
It is essential to detect partial discharge (PD) as a symptom of insulation breakdown in high voltage (HV) applications. However accuracy of such measurement is often degraded due to the existence of noise in the signal. Wavelet Transform (WT) seems to be more suitable than traditional Fourier Transform in analyzing signals with interesting transient information such as partial discharge (PD) signals. In this paper a WT method with soft thresholding is used for signal denoising. PD signals and corona obtained from actual measurements with different voltage magnitudes are processed. Processed signals show the better result.